2002
DOI: 10.1038/sj.gt.3301712
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral administration of an adenovirus expressing a kinase dead form of ErbB-2 inhibits tumor growth

Abstract: ErbB-2 is amplified or overexpressed in a number

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Ongoing studies have shown some success in the treatment of several carcinomas in animal models including lung, pancreas, and gastric cancers (42)(43)(44). For breast cancer, in vitro studies targeting several genes, such as maspin, cyclooxygenase 2, ErbB-2, and others, have shown promising results concerning the possible use of gene therapy as a treatment modality (45,46). Another potential prospect for therapeutic intervention is the possible use of siRNA technology in disease therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing studies have shown some success in the treatment of several carcinomas in animal models including lung, pancreas, and gastric cancers (42)(43)(44). For breast cancer, in vitro studies targeting several genes, such as maspin, cyclooxygenase 2, ErbB-2, and others, have shown promising results concerning the possible use of gene therapy as a treatment modality (45,46). Another potential prospect for therapeutic intervention is the possible use of siRNA technology in disease therapy.…”
Section: Discussionmentioning
confidence: 99%
“…For enhancing gene therapeutic effects of breast cancer, there are several approaches including the inhibition of oncogene functioning [ 1 ], the rehabilitation of the tumor suppressor genes [ 2 ], enhancement of the immune response of tumor cells or immunological cells [ 3 , 4 ], increase in the immunological tolerance at chemotherapy of normal cells [ 5 ], suppression of tumor angiogenesis [ 6 ], and the transformation of some apoptotic genes into tumor cells [ 7 ], as well as suicide gene therapy [ 8 ]. The last approach, which can offer the prospect of selectively introducing genes into cancer cells, rendering them susceptible to specific antitumor drugs, is especially appealing for this bystander effect [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are scattered studies of 'natural products' and pharmacologic agents that modulate signaling or expression of HER2 [314][315][316][317]. Preclinical studies in a murine breast cancer model of an adenovirus encoding kinase dead HER2/neu have been conducted as a potential mechanism to downregulate HER family signaling and take advantage of the promiscuity of heterodimerization with HER2/neu [318]; based on the biology of the HER family it is predicted that this strategy would have its greatest effect in tumors with high HER3 expression. The role of these pathway modulators remains to be determined, but the HSP90 inhibitors in particular are showing substantial promise and have the potential to circumvent resistance to other therapeutic agents.…”
Section: Her2/neu Antigen-specific Immunotherapymentioning
confidence: 99%